The Relation Between Pain After Using Fixed Orthodontic Appliance and Follow-Up Compliance of Patients in Kusuma Dental Care Clinic - Susi Meiandari; Taadi Taadi; Aryani Widayati (Jurnal Kesehatan Gigi, 2020)
People’s awareness to maintain dental and oral health continues to increase, including by orthodontic treatment. However, during orthodontic treatment period, patients may have a lot of complaints and discomfort, such as pain. Cooperative patient determines the outcome of orthodontic treatment. It can be seen from patient’s compliance to dentist’s instruction for regular follow-up. The research purpose was to determine the relation between pain after applying fixed orthodontic appliance and follow-up compliance of patients in Kusuma Dental Care Clinic. This research design uses correlational. The research was performed on September - December 2017. The population was all patients who used fixed orthodontic appliances who went to Kusuma Dental Care Clinic. Samples were collected by accidental sampling technique. Data analysis used Kendall’s tau correlation test. The research result showed that 15 respondent (48.4 %) had moderate pain after applying fixed orthodontic appliance and 18 respondent  (58.1 %) comply with order for follow-up. There is no significant relation between pain after applying fixed orthodontic appliance and follow-up compliance of patients in Kusuma Dental Care Clinic (ρ=0,509).